Effect of Bio-chemical Fertilizer on Proline Accumulation, Catalase and Peroxidase Enzymes Activity in Leaves of Two Wheat Cultivars (Ipa99 and Rabyaa) Under Water Deficit Stress. - M. Jawad, Mokdad.; W. Al-Shahwany, Ayyad; H .Khudhair, Saad. (Iraqi Journal of Science, 2023)
Field experiment was carried out during 2013- 2014 at the research field of theDepartment of Biology, College of Science, Baghdad University, to study theeffect of bio-chemical fertilizers and chemical fertilizers on some agronomic traitsand yield components of two wheat cultivars (IPA99 and Rabyaa) under droughtstress conditions. The bio-chemical fertilizers were mixture of (Azotobacterchroococcum. Azospirillum brasilense. and Pseudomonas fluorescens.) withchemical fertilizers (only 50% of the recommended dosage of N and P), while thechemical fertilizers was 100% of recommended dosage of N and P. Field plots(1×1 m) were randomly made in the field equipped with rainfall shelter to avoidrains. Grains of wheat cultivars were sown manually in their respective plots in rowswith a distance of 20 cm between rows and at seed rate of 3 g per row (150 kg/ha).The experiment was conducted in randomized complete block design (RCBD) undersplit plot arrangement with five replications. Adding fertilizer were kept in the subplot, while water stress treatment was assigned as main plot. The data were analyzedby analysis of variance (ANOVA). Water stress was applied by irrigated the plots tothe soil field capacity then withheld next irrigation until the soil moisture of therespective plots depleted to 80 (control), 30 % of soil field capacity. The results alsoshowed significant decrease antioxidant enzymes activity with the decreased waterstress. Also, the antioxidant enzymes activity (CAT and POD) were more activityafter 107 days than 65 days because of no irrigation for harvesting preparation.Besides, at high drought level, the response of the antioxidant enzymes activity(CAT and POD) and proline accumulation were similar to that observed in controltreatment, while with bio-chemical fertilizers the significant decreased respectively.These bio-chemical fertilizers would play key role in productivity and sustainabilityof protect the environment as eco-friendly fertilizers and cost effective inputs for thefarmers. With using bio-chemical fertilizers that contain different microbial strainshas led to decrease in the use of chemical fertilizers, which can be help achievingsustainability of farms and with no harmful agrochemicals for human safety.